THE INTERFACIAL LAYER FORMATION OF THE AL2O3/SI STRUCTURES GROWN BY LOW-PRESSURE METALORGANIC CHEMICAL-VAPOR-DEPOSITION - KIM, TW; KANG, WN; YOON, YS; YOM, SS; LEE, JY; KIM, CY; LIM, H; PARK, HL (AMER INST PHYSICS, 1993)
Metalorganic chemical vapor deposition of Al2O3 using Al(O-C3H7)3 and N2O via pyrolysis was investigated with the goal of producing Al2O3 epitaxial films on p-Si (100) substrates. Room-temperature capacitance-voltage measurements clearly showed metal-insulator-semiconductor behaviors for the samples with the Al2O3 insulator gate, and the interface state densities at the Al2O3/p-Si interface were approximately 10(11) eV-1 cm-2 at the middle of the Si energy gap. Auger depth profiles demonstrated that the Al2O3/Si interface was not abrupt, and transmission electron microscopy verified the formation of an interfacial layer in the Al2O3/Si interface and the formation of a polycrystalline Al2O3 thin film. These results indicated that the failure to form Al2O3 epitaxial films was due to the formation of an interfacial layer prior to the growth of the Al2O3 layer.
Keywords: THIN-FILMS